Labour market consequences of a transition to a circular economy A review paper - Laubinger, Frithjof (OECD Environment Working Papers, 2020)
Resource efficiency and circular economy policies aim at reducing resource intensity and use throughout the economy, thereby decreasing environmental impacts. Besides the environmental benefits expected from these policies, potential employment benefits are often emphasised, which would follow the anticipated structural changes in the economy from material-intensive to more labour-intensive activities. However, the size of the employment effect is still unclear and difficult to quantify. To date, the quantitative literature on the employment impacts of the circular economy is still scarce. This study is the first of its kind to review the available studies on this increasingly important policy issue